Implementation of Authentic Assessment in Al-Islam and Muhammadiyah Learning at Junior High School: Implementasi Penilaian Otentik Dalam Pembelajaran Al-Islam dan Kemuhammadiyahan di SMP - Wibowo Amin; Budi Hariyanto (Academia Open, 2021)
Education is a series of processes with the main mission of turning on human nature as a being with good character and being educated. With these efforts, it is able to encourage the ability to think, work, behave, and behave towards a human who is perfect in mind, body, and spirit. In the world of education, basically the evaluation of learning cannot be separated from the conditions of the times. One form of learning evaluation to measure student achievement in the 2013 curriculum is authentic assessment. Authentic assessment is an assessment that is carried out comprehensively to assess the input and output of students' learning. The purpose of this study was to determine the implementation and constraints in the application of authentic assessment in learning Al-Islam and Muhammadiyah at SMP Muhamamdiyah 3 Kutorejo . The research method used was qualitative research. The subjects used in this study were teachers and students of SMP Muhammadiyah 3 Kutorejo. Types and sources of data used are primary and secondary data sources. While the data collection technique is by means of observation, interviews and documentation. Meanwhile, data analysis and interpretation techniques are used, namely data reduction, data presentation and data verification. The results obtained in this study indicate that the implementation of authentic assessment in learning Al-Islam and Kemuhamamdiyahan at SMP Muhammadiyah 3 Kutorejo has been implemented well.